Climate change 2014 : impacts, adaptation, and vulnerability : Working Group II contribution to the fifth assessment report of the Intergovernmental Panel on Climate Change - Field, Christopher B.; Barros, Vicente R.; Intergovernmental Panel on Climate Change. Working Group II (New York, NY : Cambridge University Press, 2014)
This work focuses on why climate change matters and is organized into two parts, devoted respectively to human and natural systems and regional aspects, incorporating results from the reports of Working Groups I and III. The volume addresses impacts that have already occurred and risks of future impacts, especially the way those risks change with the amount of climate change that occurs and with investments in adaptation to climate changes that cannot be avoided. For both past and future impacts, a core focus of the assessment is characterizing knowledge about vulnerability, the characteristics and interactions that make some events devastating, while others pass with little notice.--
Part A. Global and sectoral aspects - Part B. Regional aspects.
Includes bibliographical references and index.
Also issued online.
Keywords: Climatic changes; Global environmental change; Climatic changes -- Government policy; Climatic changes -- International cooperation